DISCOUNT GOODS CONSUMPTION IN ISLAMIC ECONOMICS PERSPECTIVE - Sheema Haseena Armina (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This study aims to analyze discount goods consumption in the view of the Islamic economics perspective. The consumers are attracted to this a lot because of low prices and the scarce bid product however this is impressed a waste of money for consumption and purchase something. This research is a qualitative descriptive with primary data supported by the interview with the purposive method. The informants are female students of the university. The findings of this research are nothing wrong with the discount goods but this tend to make many consumers purchase more product which the orientation of consumption not only about spending money and purchasing a product for personal pleasure but it supposed to spread welfare and happiness through ZISWAF as a tool for charity. The implication of this research that people should be wise to fulfill the needs neither the wants if it is necessary.